Pengaruh Penggunaan Teknologi dalam Pembelajaran Terhadap Motivasi Belajar Siswa - Yanto, Sri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The use of technology in learning is increasingly becoming an important focus in the world of modern education. This article aims to analyze the influence of the use of technology in the learning process on student learning motivation. This research used a survey method involving 100 students from various levels of education as respondents. The research results show that the use of technology in learning has a significant positive influence on students' learning motivation. Students who are exposed to technology tend to be more motivated, actively involved in the learning process, and show increased academic achievement.